Analysis of Technology-Based Learning Using Tiktok at KB Labschool UNP Kediri - Osy Harisa; Anik Lestariningrum; Widi Wulansari (Journal of Early Childhood Development and Education, 2024)
The purpose of this research is to analyze how technology-based learning uses tiktok at KB Labschool UNP Kediri. This research uses a descriptive qualitative approach. This study has a total of 11 children consisting of 5 boys and 6 girls. The instruments used by researchers are observation and documentation. Data analysis techniques through the stages of data reduction, data presentation, and descriptive qualitative conclusions using narrative as a description of the results of the conclusion. The conclusion of the results of this study is that technology-based learning using TikTok can effectively develop physical motor and social emotional aspects in children. Children's abilities are seen in the form of increasing self-confidence and performing in public.